Archescape : on the tracks of Piranesi. - Wallis de Vries, Gijs (Amsterdam : Duizend & Een, 2014)
What might Gianbattista Piranesi (1720-1778) contribute to today's architectural debate? Could his vision of a pensile city inspire the city of tomorrow? Archescape is a new concept based on a reading of Piranesi's 'Campo Marzio', his sublime reconstruction of ancient Rome. Archescape, a fusion of the words architecture and escape into a new 'scape' addresses two issues: the city flight that tends towards the destruction of what it looks for, and the sprawling urban footprint that is unsustainable and blocks escape. It also conceives a way out: the creation of flight lines inside a dense city. What are flight lines? Can architecture frame them? Do they avoid the fatalities that affect the longing for escape? Could they minimize the impact on the earth while maximizing the contact with nature? The book consists of three parts: a manifesto, a treatise, and a reverie. The escapist manifesto formulates an architectural theory on the basis of the flight line conceptualized by Gilles Deleuze: neither a line between two points, nor a derived function, but a line 'in between' motivated by a primary drive that engages imagination, movement, and design. The treatise of the pensile city analyzes the verbal and visual discourse of Piranesi's 'Campo Marzio', considering both his other works and his position in his time. The reverie discusses contemporary interpretations of the Campo Marzio as a negative or positive utopia, as a Manhattanist archipelago, or as a field of walls, and culminates in strolls through a future archescape. The text is illustrated by many images, a selection of which is reproduced in visual essays.
boek
Keywords: Piranesi, Giovanni Battista